Review of the Rare Genus Phrynomedusa Miranda-Ribeiro, 1923 (Anura: Phyllomedusidae) With Description of a New Species - Baeta, Delio [UNESP]; Menta Giasson, Luis Olimpio; Pombal, Jose P.; Baptista Haddad, Celio Fernando [UNESP] (Herpetologists League, 2016)
We present the first taxonomic review of the genus Phrynomedusa since its description with diagnoses of the genus and species. We present a broad literature review of the genus and provide updates and remarks about the type series, tadpoles, calls, geographic distribution, and natural history of the species of Phrynomedusa. Additionally we describe a new species from municipio de Sao Luiz do Paraitinga, state of Sao Paulo, Brazil. Phrynomedusa dryade was initially identified as Phrynomedusa marginata; however, an integrated analysis of morphological and molecular characters enabled its recognition as a separate new species. For the first time, the advertisement call for one species of Phrynomedusa is described in detail. We describe the tadpole and present some field notes about the activity and biology of this new species.
Keywords: Atlantic Forest; Phrynomedusa dryade sp nov.; Tadpole; Taxonomy; Vocalization